Stability and behaviour of parallel-sided workpieces held by a robot gripper [Bir robot tutucusu tarafindan yakalanmiş paralel yüzlü i̇ş parçalarinin kararliliǧi ve hareketi] - (:unkn) unknown (My University, 1998)
The stability and behaviour of parallel-sided workpieces held by a two-fingered robot gripper were investigated. The behaviour of the workpiece under an external force was studied by computer simulation through modelling the actual gripper-workpiece system as a mechanism with a single degree of freedom. The characteristics of the possible slip motion of the workpiece were also investigated, taking into consideration the effects of kinematic parameters on grasping stability. © TÜB|TAK.
Keywords: Kinematic similarity; Mechanisms; Robot grippers; Stability